Osmoregulation in Atlantic salmon Salmo salar smolts transferred to seawater at different temperatures. Issue 4 (7th August 2014) - Handeland, S. O.; Imsland, A. K.; Nilsen, T. O.; Ebbesson, L. O. E.; Hosfeld, C. D.; Pedrosa, C.; Toften, H.; Stefansson, S. O.
<x xml:space="preserve">Abstract</x> In order to investigate how changes in gill Na+, K+‐ATPase (NKA) α1a and α1b subunits, Na+, K+, 2Cl− co‐transporter (NKCC1) and the apical cystic fibrosis trans‐membrane conductance regulator‐I (CFTR‐I) transcripts in wild strain of Atlantic salmon, Salmo salar, smolts are affected by temperature during spring, hatchery‐reared parr (mean ± s.e. fork length = 14·1 ± 0·5; mean ± s.e. body mass = 28·5 ± 4·5 g) originating from broodstock from the Vosso river (western Norway) were acclimated to three temperature regimes (4·1, 8·1 and 12·9° C) in May and reared under gradually increasing salinity between May and June. Changes in plasma Na+, haematocrit (Hct) and PCO2 were monitored in order to assess and compare key physiological changes with the transcriptional changes in key ion transporters. The temperatures reflect the natural temperature range in the River Vosso during late spring. Overall, higher gill NKA α1b mRNA levels, gill NKCC1a levels and CFTR‐I levels were observed in the 4·1° C group compared to the 11·9° C group. This coincided with a 2–3 week period with decreased Hct and PCO2 and may indicate a critical window when smolts suffer from reduced physical performance during migration. Further research is needed to confirm the potential interaction between ecological and physiological conditions on mortality of hatchery‐reared smolts from River Vosso during their natural migration.